Arabic Christian Theology - Najib George Awad (St Andrews Encyclopaedia of Theology, 2023)
This entry starts by exploring the meaning of the term ‘Arabic Christian theology’ to explain its oxymoronic nature. It then introduces the form of Christian theological thought that one can find in the Arabic-speaking regions of the Middle East and North Africa (MENA). It offers a brief historical narrative of some of the main milestones on the trajectory of the Arab-Eastern Christian theological traditions. Then it primarily focuses on various forms of Arab-Eastern Christianity and its theological reasoning in today’s MENA region. It briefly presents some of the primary trends in theological discourse which these Christians develop in their present life-setting, including a discussion of the key figures and the main theological methods these Christians opted for throughout their history. These trends will be explored in their regional context, especially focusing on countries including Lebanon, Syria, Palestine/Israel, and Egypt. This entry concludes with an analytical assessment and scrutiny of the components and features of these theological trends, followed by some remarks on the potential future of Arab-Eastern Christian theology.